Electrical conductive and photoelectrical properties of heterostructures based on gallium and chromium oxides with corundum structure - Almaev, Dmitry A.; Almaev, Aleksei V.; Kopyev, Viktor V.; Nikolaev, Vladimir I.; Pechnikov, Aleksei I.; Stepanov, Sergey I.; Boyko, M. E.; Butenko, Pavel N.; Scheglov, Mikhail P. (Technical physics letters)
α-Ga2O3/α-Cr2O3 heterostructures with a corundum structure were obtained by chloride vapor phase epitaxy and magnetron sputtering. The structural, electrical conductive and photoelectrical properties of the obtained samples were studied. It was established that the α-Ga2O3/α-Cr2O3 heterostructures exhibits weak rectifying properties and in comparison with α-Ga2O3 films has a higher response speed when exposed to ultraviolet radiation